Empirical examination of macro-economic factors on credit risk determinant of commercial banks in Jordan. - Alrfai, Mohammad Motasem Sayel (2022)
The high volume of risks facing banks is one of the most important reasons behind their failure. After the financial crisis of 2008, the concern toward credit risk management took a new level. The credit risk management behavior and decisions tend to increase the credit risk level. Consequently, appropriate amount of information may enhance the management perception about the effect of some factors on credit risk. The relationship between macroeconomic factors and credit risk increased incredibly especially after the financial crisis. So, it is important to understand the mechanism of macroeconomic factors and how they relate to the management behaviour to decrease credit risk. This study investigated the existence of a relationship between some of the macroeconomic factors as independent variables and the bank’s credit risk in Jordan. The dependent variable is credit risk, which is measured by the non-performing loans (NPL) to total loans ratio. This research used three theories including financial acceleration theory, agency theory, and information asymmetry theory. The sample of the study is 16 Jordanian banks listed on the Amman stock exchange from 2008 to 2019. To test the hypotheses of the current study, a random effect model using STATA software was employed. The result showed that foreign direct investment (FDI) and the output gap affected credit risk significantly and negatively. The result specified that as remittance (REMIT) grows, credit risk considerably accelerated, and the same effect was also recognised for public debt (DEBT). The outcomes revealed an important influence of tax on personal income (TAXINC). The findings of the current study have implications for investors, regulators, and market participants by affording a considerable indication that the macroeconomic factors are related to credit risk and thus, can explain the phenomenon of NPLs.